A graphene-based transition metal single-atom catalytic material and preparation method thereof
By doping nitrogen and transition metals into graphene-based materials, a single-atom catalytic material of graphene-based transition metal was prepared, which solved the problems of weak loading capacity of powdered catalysts and difficulty in recycling and reuse, and achieved high-efficiency loading and film-forming thin-film catalytic material, with excellent recycling and reuse performance and green and sustainable development advantages.
Patent Information
- Application Number
- CN202211707205.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing transition metal single-atom catalysts are prepared in powder form, and there are problems such as weak load capacity and difficulty in recycling and reuse.
Highly conductive graphene is used as a support and graphene-based transition metal single-atom catalytic material is prepared through nitrogen doping and transition metal doping. Using the self-assembly performance of the precursor functional groups and excellent film formation properties, loading and forming films are carried on the surface of a variety of substrates to realize the preparation of thin-film catalytic materials.
It has achieved efficient loading and film formation of catalytic materials, has excellent recycling and reuse performance, and has less pollution to liquid phase catalysis, especially water catalysis, and has the advantage of green and sustainable development.
Smart Images

Figure CN116273112B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of graphene materials, and in particular to a graphene-based transition metal single-atom catalytic material and a preparation method thereof. Background Art
[0002] The cutting-edge research in heterogeneous catalysis technology is metal single-atom catalysis technology. Metal single-atom catalysis refers to a special type of catalytic material with a single isolated stable metal atom as the active site. The isolated metal atoms in metal single-atom catalysis are different from electrically neutral atoms and gas-phase free atoms in the physical sense. Instead, they are isolated active atoms that interact with the carrier and exist stably. At present, most of the metals used in metal single-atom catalytic materials are precious metals, and it is particularly necessary to develop transition metal single-atom catalytic materials with excellent performance. However, due to the extremely high surface energy of isolated metal atoms, it is difficult to naturally load them on the surface of the carrier. Therefore, the stable anchoring of isolated metal atoms can only be achieved through the method of surface atomic coordination.
[0003] At present, most transition metal single-atom catalysts are prepared in powder form, but powder materials often have problems such as weak loading capacity and difficulty in recycling and reuse. Summary of the invention
[0004] In view of the above problems, the present invention provides a graphene-based transition metal single-atom catalytic material and a preparation method thereof. The graphene-based transition metal single-atom catalytic material described in the present invention is a graphene-based transition metal single-atom catalytic material obtained by nitrogen doping and transition metal doping with highly conductive graphene as a carrier. The purpose of nitrogen doping is to use the strong electronegativity of nitrogen atoms to capture transition metal atoms and form stable coordination bond interactions to obtain stable transition metal atoms in active centers. In addition, in view of the pain points of weak loading capacity and difficult recycling of traditional powdered catalysts, the graphene-based transition metal single-atom catalytic material provided by the present invention utilizes the self-assembly performance of its precursor functional groups and excellent film-forming performance and adhesion. It can be loaded and film-formed on the surface of various substrates (such as carbon fiber cloth, screen, etc.), and has great advantages in recycling and reuse. Because of its recyclable and reusable characteristics, it is more environmentally friendly. Its application in the field of liquid phase (such as water body) catalytic degradation will help promote the green and sustainable development of catalytic materials.
[0005] On the one hand, a method for preparing a graphene-based transition metal single-atom catalytic material is provided, and the specific steps are as follows:
[0006] (1) Dissolve transition metal-containing acetate and glutamic acid in deionized water to obtain a precursor solution A.
[0007] Weigh appropriate amounts of acetate containing transition metals and glutamic acid and stir them at 60-80° C. until they are completely dissolved in water to prepare a precursor solution A. The acetate containing transition metals can provide a transition metal source for subsequent reactions, and glutamic acid can be used as a nitrogen source to nitrogen-dope graphene in subsequent reactions.
[0008] Preferably, the acetate of the transition metal is nickel acetate tetrahydrate, which is stirred with glutamic acid at 60-80° C. until completely dissolved in water to prepare an aqueous solution containing 0.1-0.5 mM nickel acetate tetrahydrate and 5-20 mM L-glutamic acid to obtain a precursor solution A.
[0009] (2) Adding graphene oxide cake with a solid content of 50% to precursor solution A to obtain precursor solution B.
[0010] An appropriate amount of graphene oxide wet cake (solid content of 50%) is weighed and added to the precursor solution A. The mixture is stirred at 1500-2500 r / min using a digital stirrer at room temperature until the graphene oxide cake is completely dispersed. A dispersion containing 0.5-1.2% by mass of graphene oxide is prepared to obtain a precursor solution B. The beneficial effect of the 0.5-1.2% by mass fraction of graphene oxide dispersion is that the solid content can ensure that the graphene oxide is fully dispersed in the aqueous solution system, thereby ensuring that the graphene oxide and the components in the precursor solution A are fully dispersed and subsequently uniformly loaded. If the solid content is too high, the slurry state will be relatively thick, which is not conducive to dispersion or reaction.
[0011] (3) Immerse the substrate in the precursor solution B, then take it out, air dry or bake it, and transfer it to a tube furnace.
[0012] The substrate base material can be selected from carbon fiber cloth, screen mesh, etc. Preferably, the substrate base material is selected from carbon fiber cloth, and the carbon fiber cloth is first subjected to acidification pretreatment, and the carbon fiber cloth is placed in a 0.1-1M nitric acid solution at 50-80°C for 1-4h, and then washed with deionized water for multiple times until the pH value of the solution is neutral, and then taken out to dry naturally or dried in an oven at 60-90°C. The carbon fiber cloth is pretreated with nitric acid so that the substrate has hydrophilic functional groups, which can make the carbon fiber cloth substrate easier to be infiltrated and have a more ideal load capacity.
[0013] The substrate base material is immersed in the precursor solution B for 0.5-2h, taken out and dried naturally or in an oven at 60-90℃. Since the glutamic acid in the precursor solution B is a broken chain small molecule organic substance with carboxyl functional groups at both ends, its carboxyl functional groups can form a film with the hydroxyl functional groups on the graphene oxide through dehydration bonds. Therefore, by utilizing the self-assembly properties and excellent adhesion of the precursor functional groups, a film can be formed on the surface of the substrate base material through immersion and drying, thereby obtaining an ultra-thin film-type catalytic material.
[0014] (4) Under a nitrogen protective atmosphere, ammonia and hydrogen are introduced successively to obtain a transition metal single atom-N-RGO catalytic material supported on a substrate.
[0015] The temperature and flow rate of nitrogen, ammonia and hydrogen are as follows: the nitrogen flow rate is set to 00-200sccm, the temperature is raised to 500°C, and the temperature is kept for 2-4h, and the heating rate is 5°C / min; after the 500°C insulation is completed, a mixed gas of ammonia and nitrogen is introduced, the flow rate is set to 100-200sccm, the temperature is raised to 600-800°C, and the heating rate is 2°C / min. After reaching the target temperature, the heating is stopped after keeping the temperature for 1-3h. The flow rate of the mixed gas of hydrogen and nitrogen is set to 50-150sccm, and the gas is ventilated for 10-30min. Finally, pure nitrogen protection is switched and the mixture is naturally cooled to room temperature. The volume ratio of the mixed gas of ammonia and nitrogen is 7:(1-3), and the volume ratio of the mixed gas of hydrogen and nitrogen is 1:(7-9).
[0016] The high temperature of 600-800°C can reduce the graphene oxide attached to the surface of the substrate material into graphene;
[0017] The introduction of ammonia gas can further dope graphene with nitrogen. Since the electronegativity of nitrogen atoms is greater than that of carbon atoms and their atomic radius is moderate relative to carbon atoms, nitrogen doping into graphene can break the local electrical neutrality of graphene, improve its conductivity, state density and band gap, and thus significantly improve the overall conductivity and catalytic properties of graphene.
[0018] The introduction of hydrogen can activate single transition metal atoms, preventing them from being oxidized and losing their activity.
[0019] Through the above method, what is finally obtained is a single-atom catalytic material with nitrogen-doped auxiliary transition metal single atoms coordinated with graphene as the supporting substrate. The single-atom catalytic material is supported on the substrate in the form of a thin film and has better recycling and reusability than powdered catalytic materials.
[0020] The graphene-based transition metal single-atom catalytic material prepared by the above method is applied in the field of liquid phase catalysis. This catalytic material has excellent photocatalytic and electrocatalytic properties, and because it is in the form of a thin film, it has excellent recyclability and reuse performance, and has less pollution to liquid phase catalysis, especially water catalysis, and has the advantage of green and sustainable development.
[0021] The beneficial effects of the present invention are:
[0022] 1. The graphene-based transition metal single-atom catalytic material provided by the present invention utilizes the self-assembly performance and excellent adhesion of the precursor functional groups to form a film on the surface of the supporting substrate by soaking and drying to obtain an ultra-thin film-type catalytic material, which has excellent recyclability and reuse performance, has less pollution to the liquid phase catalysis, especially the water body catalysis field, and has the advantage of green and sustainable development;
[0023] 2. A graphene-based transition metal single atom catalytic material and a preparation method thereof provided by the present invention, through glutamic acid and ammonia assisted pyrolysis reaction, to ensure nitrogen doping, using the strong electronegativity of nitrogen atoms to provide active sites for capture and stable coordination of transition metal single atoms;
[0024] 3. The present invention provides a graphene-based transition metal single atom catalytic material and a preparation method thereof, which activates the transition metal single atoms through high-temperature activation in a H2 atmosphere to prevent them from being in an oxidized state and losing their activity, thereby further ensuring the catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of a graphene-based transition metal single-atom catalytic material prepared in Example 1 of the present invention.
[0026] Figure 2 The photocurrent and dark current diagrams of a graphene-based transition metal single-atom catalytic material prepared in Example 1 of the present invention under a micro voltage (-0.3-0.6V). DETAILED DESCRIPTION
[0027] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings, which form a part of the description, in which exemplary embodiments of the present invention are shown as examples, wherein the features of the present invention are identified by reference numerals. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best way to perform the present invention, and is sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description and the accompanying drawings should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0029] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0030] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0031] Example 1
[0032] This embodiment provides a method for preparing a graphene-based transition metal single-atom catalytic material:
[0033] 1) Using deionized water as solvent, weigh appropriate amounts of nickel acetate tetrahydrate and glutamic acid and stir at 60°C until completely dissolved in water, preparing an aqueous solution containing 0.3 mM nickel acetate tetrahydrate and 10 mM L-glutamic acid to obtain a precursor solution A;
[0034] 2) After the precursor solution obtained in step 1) cools to room temperature, weigh an appropriate amount of graphene oxide wet cake (solid content 50%) and add it to the precursor solution A, stir at room temperature with a digital stirrer at a speed of 2000 r / min until the graphene oxide cake is completely dispersed, and prepare a dispersion containing 1% by mass of graphene oxide to obtain a precursor solution B;
[0035] 3) Place the carbon fiber cloth in a 0.5M nitric acid solution at 70°C for 1-4h, then wash it with deionized water several times until the pH value of the solution is neutral, then take it out and dry it naturally or dry it in an oven at 80°C for use, to obtain a pretreated carbon fiber cloth, immerse the pretreated carbon fiber cloth in the precursor solution B obtained in step 2) for 0.5-2h, take it out and dry it naturally or dry it in an oven at 80°C;
[0036] 4) Transfer the sample obtained in step 3) to a tube furnace, pass nitrogen protection, set the nitrogen flow rate to 200 sccm, heat to 500℃, keep warm for 2h, and the heating rate is 5℃ / min; after the 500℃ heat preservation, switch to NH3 / N2=7:3 V / V Mixed gas, the mixed gas flow rate is set to 200sccm, the temperature is raised to 700℃, the heating rate is 2℃ / min, after reaching the target temperature, keep warm for 2h and then stop heating, switch H2 / N2=1:9 V / VMixed gas, the mixed gas flow rate is set to 100 sccm, ventilation for 15 minutes, then switch to pure nitrogen protection and naturally cool to room temperature, to obtain an ultra-thin film type Ni-N-RGO catalytic material with carbon fiber cloth as the base, and the target catalytic material is a single-atom catalytic material with nitrogen-doped assisted nickel single atom coordination with graphene as the loading substrate.
[0037] The final product was tested for photocatalytic hydrogen evolution reaction performance: the ultra-thin film-type catalytic material Ni-N-RGO with carbon fiber cloth as the substrate was used as the pole piece to connect to the working electrode of the electrochemical workstation, and the calomel electrode was used to connect to the reference electrode of the electrochemical workstation; the Pt electrode was used to connect to the counter electrode of the electrochemical workstation. The three electrodes were placed in a transparent square quartz electrolytic cell, and an aqueous solution containing 0.5mM sodium chloride and 0.1mM hydrogen chloride was prepared as an electrolyte, which was loaded into the square transparent quartz electrolytic cell and immersed in the three electrodes. A xenon lamp was used as a visible light source, and the light source was facing the square transparent quartz electrolytic cell at a distance of 10cm. A micro-voltage difference was given to the counter electrode and the working electrode through the electrochemical workstation. When the xenon light source was turned on, fine bubbles gradually appeared on the surface of the working electrode and the Pt electrode. The light source was intermittently blocked with opaque cardboard to test the photocurrent and dark current of the working electrode. The test results showed that 3mA / cm 2 Photocurrent: 9mA / cm2 at 0.6V positive voltage 2 The current density is 10000, and there is almost no dark current when the light is blocked. The amount of photogenerated electrons and holes is the key to the performance of photocatalytic materials. The more photogenerated electron-hole pairs are generated, the greater the photogenerated current density is, which indicates that the catalytic material has very ideal photocatalytic performance.
[0038] Example 2
[0039] The difference between this embodiment and embodiment 1 is that glutamic acid is not used in step 1), and ammonia is not introduced in step 4), that is, there is no nitrogen doping treatment in the entire preparation process, and the other steps are the same as those in embodiment 1. The purpose is to explore the effect of nitrogen doping on the performance of the catalytic material. The photocatalytic hydrogen evolution reaction performance test consistent with embodiment 1 is carried out. The test results show that when no external micro voltage (0V) is applied, 0.17mA / cm 2 Photocurrent: 0.85mA / cm2 at 0.6V positive voltage 2 The current density is 2.33 W, and the dark current is almost zero when the light is blocked. This can be attributed to the fact that without glutamate, the nickel atoms cannot be independently anchored and an efficient single-atom catalytic material cannot be formed.
[0040] Example 3
[0041] The difference between this embodiment and embodiment 1 is that hydrogen is not introduced in step 4), and the other steps are the same as those in embodiment 1. The purpose is to explore the effect of the introduction of H2 on the activity of transition metals, that is, the effect on the performance of catalytic materials. The photocatalytic hydrogen evolution reaction performance test consistent with embodiment 1 is carried out. The test results show that when no external micro voltage (0V) is applied, 0.44mA / cm 2 Photocurrent: 1.33mA / cm2 at 0.6V positive voltage 2 The current density of the photocatalytic device is 0.13 W, and the dark current is almost zero when the light is blocked. This can be attributed to the lack of thermal activation process during heat treatment under hydrogen atmosphere, resulting in lower photocatalytic performance.
[0042] Example 4
[0043] The difference between this embodiment and embodiment 1 is that the Ni-N-RGO / carbon fiber cloth electrode obtained in step 5) is used as a photocatalytic electrode to explore the photocatalytic degradation ability of the Ni-N-RGO catalytic material for a 1M concentration of rhodamine aqueous solution. The specific experiment is: prepare 20ml of a 1M concentration of rhodamine aqueous solution, immerse the Ni-N-RGO / carbon fiber cloth electrode vertically in the solution, use a xenon lamp as a light source, and the distance between the light source and the transparent quartz tank is 10cm. Turn on the xenon lamp light source for photodegradation test, take 1ml of solution every 5 minutes to observe the color of the solution, and find that the solution tends to be clear and transparent after 15 minutes, indicating that the Ni-N-RGO catalytic material has a very ideal photocatalytic degradation ability for rhodamine.
[0044] Example 5
[0045] The difference between this embodiment and embodiment 4 is that there is no immersion treatment of the precursor B in the carbon fiber cloth, but the precursor solution B obtained in step 2) is directly obtained by a spray granulator to obtain a precursor powder, and then heat-treated under the same conditions as step 4) to obtain Ni-N-RGO powder as a photocatalytic degradation material, and to explore the photodegradation ability of Ni-N-RGO powder. The specific test experiment is: prepare a 1M concentration of rhodamine aqueous solution, weigh Ni-N-RGO powder and disperse it in the rhodamine aqueous solution, stir it with a magnet, use a xenon lamp as a light source, and the distance between the light source and the transparent quartz tank is 10cm. Turn on the xenon lamp light source, start the magnetic stirrer, and perform a photodegradation test under magnetic stirring conditions. Take 1ml of solution every 5 minutes and filter it with a filter tip. Observe the color of the solution. It is found that the solution tends to be clear and transparent after 10 minutes, indicating that the Ni-N-RGO powder catalytic material has a very ideal photocatalytic degradation ability for rhodamine.
[0046] Since Ni-N-RGO powder catalytic material has a larger contact area than thin film catalytic material, the catalytic efficiency of powder catalytic material is slightly better than that of thin film catalytic material. However, since the powder catalytic material needs to be tested for photodegradation under magnetic stirring conditions and is eventually dispersed in a liquid environment, it can no longer be recycled and reused.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a graphene-based transition metal single-atom catalytic material, characterized in that: The following steps are involved: (1) dissolving an acetate containing a transition metal and glutamic acid in deionized water to obtain a precursor solution A, wherein the acetate containing a transition metal is nickel acetate tetrahydrate; (2) adding graphene oxide wet cake having a solid content of 50% to precursor solution A to obtain precursor solution B; (3) Immersing the substrate in the precursor solution B, then taking it out, drying it in the air or by baking it, and transferring it to a tube furnace; (4) In a nitrogen protective atmosphere, ammonia and hydrogen are introduced successively to obtain a transition metal single atom-N-RGO catalytic material loaded on a substrate; the temperature and flow rate of nitrogen, ammonia and hydrogen are as follows: the nitrogen flow rate is set to 100-200sccm, the temperature is raised to 500°C, and the temperature is kept for 2-4h, and the heating rate is 5°C / min; after the 500°C insulation is completed, a mixed gas of ammonia and nitrogen is introduced, and the flow rate is set to 100-200sccm, and the temperature is raised to 600-800°C, and the heating rate is 2°C / min. After reaching the target temperature, the temperature is kept for 1-3h and then the heating is stopped. A mixed gas of hydrogen and nitrogen is introduced, and the flow rate is set to 50-150sccm. The gas is ventilated for 10-30min, and finally pure nitrogen protection is switched and naturally cooled to room temperature; Finally, the Ni single atom-N-RGO catalytic material loaded on the substrate was obtained.
2. A method for preparing the graphene-based transition metal single-atom catalytic material according to claim 1, characterized in that: The substrate base material is carbon fiber cloth, and the carbon fiber cloth needs to be pre-treated by acid washing, and the specific steps are: placing the carbon fiber cloth in an acid solution at 50-80° C. for 1-4 hours, then washing it with deionized water for multiple times until the washing solution is neutral, and then taking it out to dry naturally or bake it.
3. A method for preparing the graphene-based transition metal single-atom catalytic material according to claim 1, characterized in that: The volume ratio of the mixed gas of ammonia and nitrogen is 7:(1-3), and the volume ratio of the mixed gas of hydrogen and nitrogen is 1:(7-9).
4. A method for preparing the graphene-based transition metal single-atom catalytic material according to claim 1, characterized in that: The precursor solution A is prepared at 60-80°C.
5. A method for preparing the graphene-based transition metal single-atom catalytic material according to claim 1, characterized in that: The mass fraction of graphene oxide in the precursor solution B is 0.5-1.2%.
6. A graphene-based transition metal single-atom catalytic material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The graphene-based transition metal single-atom catalytic material is in the form of a thin film.
7. An application of the graphene-based transition metal single-atom catalytic material according to claim 6 in the field of liquid phase catalysis.
Citation Information
Patent Citations
Metal monoatomic catalyst loaded by flexible carbon-based carrier and preparation method and application of catalyst
CN110102300A
Noble metal atomic-scale dispersed electrochemical catalyst capable of being amplified in batches and preparation method thereof
CN111330569A